Descartes no es un conceptualista - Karofsky, Amy (2002)
“Descartes is not a Conceptualist”. Some contemporary interpretations of Descartes suggest that Descartes holds a conceptualist position with regard to the eternal truths. According to this reading of Descartes, modalities are determined by what is conceivable by the minds in a universe. Since what is possible depends upon what the intellects can conceive, prior to the existence of the intellects, there is no concept of possibility. Hence prior to creating a universe, it is not the case that anything is possible for God. On such an account, the conceptualist can avoid commitment to the doctrine that God can do anything. I show in this paper that the passages used to provide support for the conceptualist reading of Descartes are misinterpreted. I conclude that Descartes is not a conceptualist.